2009
DOI: 10.1016/j.neuron.2009.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Replay of Extended Experience

Abstract: Summary During pauses in exploration, ensembles of place cells in the rat hippocampus re-express firing sequences corresponding to recent spatial experience. Such ‘replay’ co-occurs with ripple events: short-lasting (~50–120 ms), high frequency (~200 Hz) oscillations that are associated with increased hippocampal-cortical communication. In previous studies, rats explored small environments, and replay was found to be anchored to the rat’s current location, and compressed in time such that replay of the complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

75
1,017
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 749 publications
(1,098 citation statements)
references
References 48 publications
75
1,017
3
3
Order By: Relevance
“…The "replay" of waking activity has been assumed to play a critical role in memory consolidation and transfer of information from the hippocampus to the neocortex (12,13,(15)(16)(17)(18), because selective elimination of ripples after task learning impairs memory performance (22)(23)(24). Recent studies also emphasized the prospective and constructive role of ripple sequences (16)(17)(18)(19). Sequential activity of CA1 pyramidal neurons during ripples and in memory tasks during theta oscillations has been implicitly assumed to be generated in the recurrent excitatory networks of the hippocampal CA3 region and inherited through synaptic activity by the CA1 neuronal population (4,12,16,21,23) although direct evidence has not been shown experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The "replay" of waking activity has been assumed to play a critical role in memory consolidation and transfer of information from the hippocampus to the neocortex (12,13,(15)(16)(17)(18), because selective elimination of ripples after task learning impairs memory performance (22)(23)(24). Recent studies also emphasized the prospective and constructive role of ripple sequences (16)(17)(18)(19). Sequential activity of CA1 pyramidal neurons during ripples and in memory tasks during theta oscillations has been implicitly assumed to be generated in the recurrent excitatory networks of the hippocampal CA3 region and inherited through synaptic activity by the CA1 neuronal population (4,12,16,21,23) although direct evidence has not been shown experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Internally generated sequences have been also described in CA1 during theta oscillations in memory tasks (4, 11), raising the possibility that a given neuronal substrate is responsible for generating sequences at multiple time scales. The extensive recurrent excitatory collateral system of the CA3 region has been postulated to be critical in this process (4,7,12,13).The sequential activity of place cells is "replayed" during sharp waves (SPW) in a temporally compressed form compared with rate modulation of place cells (14)(15)(16)(17)(18)(19)(20) and may arise from the CA3 recurrent excitatory networks during immobility and slow wave sleep. The SPW-related convergent depolarization of CA1 neurons gives rise to a local, fast oscillatory event in the CA1 region ("ripple, refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When at rest, or during pauses in exploration of a track, place cells in the rat hippocampus fire in sequences corresponding to portions of the route already traveled or about to be traveled (75). However, although these firing sequences take place over intervals that are linearly related to the distances represented, firing rates are very fast in comparison with the rat's normal rate of motion (corresponding to rates of about 8 m/s).…”
Section: Inability Tomentioning
confidence: 99%
“…Thus, despite its strong evidence for preplay, it does not conclusively answer the question of what role replay and preplay might subserve in real world navigation. One supportive indication came from Davidson, Kloosterman, and Wilson's (2009) demonstration that when rats are required to run on a straight track, ripple events get chained together for longer tracks. They suggested that this chaining might be mediated by reentrant processing between the hippocampus and entorhinal cortex, supporting the idea that replay during the SPW state might be a general mechanism employed in learning a navigational route.…”
Section: The Consumption Of Spatial Representationsmentioning
confidence: 99%